Implementasi Metode Simple Maze Wall Follower Dengan Menggunakan Free RTOS Pada Robot Maze - Agung Widya Gumelar; Dahnial Syauqy; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
One type of robot that can facilitate human activities in finding the destination in the labyrinth is Maze Wall Follower Robot, that robot can also be included in contest robot in category robot firefighter. Maze Wall Follower Robot use Simple Maze method, which follows the left wall as the main reference and the dark line as the finish point. Implementation Free RTOS is made for multitasking in measuring distances between robots and walls using ultrasonic sensors and photodiodes. Each sensor is used as system inputs made tasks that have priority 1 and L298N module Driver Motor dual H-Bridge which is used as system output made task 1. Result of measurement of wall distance measurement using ultrasonic sensor HC-SR04 which tested 7 times with different distance has 0% error, and line reading at the bottom of the maze is tested 6 times with different colors using photodiode sensor module which has 0% error. Average time result to complete goal with distance between start and finish point 959 cm and pass 23 turns and 2 dead end by Maze Wall Follower Robot which does not use Free RTOS is 75,62429 second and use Free RTOS is 68,36143 second with 7 times testing. Then the robot with Free RTOS faster 7.262857 seconds from robot without Free RTOS.